Sphere detection analysis performance combined with the LDPC decoding / Xiao Peng and Satoshi Goto - Xiao, Peng; Satoshi, Goto (UiTM Press, 2011)
This paper investigates on the low density parity-check (LDPC) decoding algorithms and the detection methods of the multiple-input multiple-output (MIMO) systems. For LDPC codes, min-sum and layered decoding algorithms are discussed, and for MIMO detection, the maximum likelihood (ML) decision based on the sphere decoding algorithm is mainly analyzed. Also, the performance of the combination of the channel coding and space time coding is presented, which use the preceding methods respectively. In this LDPC coded system, the log-likelihood ratio (LLR) is propagated from LDPC decoder to the MIMO detector and then fed back, which would increase the decoding efficiency. Analysis shows that the combination certainly improves the performance of the receiver; moreover the layered LDPC decoding has better performance in this combination system.